2015
DOI: 10.1111/hepr.12598
|View full text |Cite
|
Sign up to set email alerts
|

Hypointense hepatocellular carcinomas on apparent diffusion coefficient mapping: Pathological features and metastatic recurrence after hepatectomy

Abstract: Hypointense HCC on ADC mapping are characterized by poor histological differentiation and more frequent microscopic portal invasion, and are significantly associated with metastatic recurrences after hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…All 36 studies were cohort studies, with 33 retrospective studies [2, 7-9, 11-16, 18, 20-23, 27-44] and 3 prospective studies [45-47]. The proportions of LC were variable, with 18 studies having >50% of patients with LC [8, 13-15, 18, 23, 28, 32-34, 36, 37, 41-43, 45-47], and 18 studies having <50% of patients with LC [2, 7, 9, 11, 12, 16, 20-22, 27, 29-31, 35, 38-40, 44]. Thirteen studies had all HCC size of <5 cm [2, 9, 12, 18, 21, 28, 31-34, 39, 41, 43], 23 studies used HBA contrast-enhanced MRI [2, 7-9, 11-14, 16, 20, 21, 27-31, 33, 37-41, 44], and 24 studies used DWI [8, 11, 16, 18, 20, 22, 23, 27, 28, 30-37, 39, 40, 42, 44-47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 36 studies were cohort studies, with 33 retrospective studies [2, 7-9, 11-16, 18, 20-23, 27-44] and 3 prospective studies [45-47]. The proportions of LC were variable, with 18 studies having >50% of patients with LC [8, 13-15, 18, 23, 28, 32-34, 36, 37, 41-43, 45-47], and 18 studies having <50% of patients with LC [2, 7, 9, 11, 12, 16, 20-22, 27, 29-31, 35, 38-40, 44]. Thirteen studies had all HCC size of <5 cm [2, 9, 12, 18, 21, 28, 31-34, 39, 41, 43], 23 studies used HBA contrast-enhanced MRI [2, 7-9, 11-14, 16, 20, 21, 27-31, 33, 37-41, 44], and 24 studies used DWI [8, 11, 16, 18, 20, 22, 23, 27, 28, 30-37, 39, 40, 42, 44-47].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding multifocality, 4 studies used satellite nodules [8, 16, 23, 45] and 3 studies used ≥2 lesions [22, 30, 35] as a definition of multifocality. Regarding diffusion restriction, 4 studies were clear about the use of ADC [16, 23, 32, 39], whereas 3 were unclear [28, 34, 40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Zhou et al (4) reported that the Edmondson-Steiner grade of HCC was an independent risk factor for recurrence after resection. Mori et al (31) also demonstrated that poorly differentiated HCC was more likely to have intrahepatic metastasis and recurrence compared with well-/moderately differentiated HCC. The results from the present study revealed that the HCC patients with lower T 1(L-H)/H (%) values had lower cumulative recurrence rates compared with those patients with higher T 1(L-H)/H (%) values at the 20-min HBP.…”
Section: Discussionmentioning
confidence: 96%